PERFORMANCE CRITERIA of RUBBER UKM BASED ON COOPERATIVE USING BALANCED SCORECARD METHOD - Dessy Iriani Putri; Lukman M. Baga; Burhanuddin Burhanuddin (School of Business, IPB University (SB-IPB), 2017)
Small and Medium Enterprises (UKM) of Usaha Mandiri is the only UKM in Putri Hijau district, North Bengkulu that carries out its activities based on cooperative principles. The UKM was established in 2010 due to the rubber farmer’s concern about their future. In the last few years, the rubber price has declined, resulting in the decreasing performance of UKM Usaha Mandiri’s. The objective of this research is to analyze the performance of UKM of Usaha Mandiri. The method used is balanced scorecard (BSC) and Focus Group Discussion (FGD) to identify the UKM’s strategic aim and the BSC value. The result of the research shows that the performance of UKM of Usaha Mandiri started to decline from 2013–2015. The BSC score from 2011–2015 was 112.93 (excellent), 141.84 (excellent), 95.41 (excellent), 47.42 (average) and 81.62 (very good). The decline of the performance was due to the decline of natural rubber price. The conclusion for the research is that in 2015 the performance of UKM of Usaha Mandiri was categorized as very good (BSC method) with the most contribution from growth and learning perspective. Keywords : Balanced scorecard, BSC, cooperation, performance measurement, UKM